EDUCATION AND CARE SIMULATION: IMPROVING FAMILY CAPACITY IN PREVENTING PRESSURE WOUNDS IN IMMOBILIZED ELDERLY - Feny Marlena; Veby Fransisca Rozi; Septi Andrianti (Jurnal Pengabdian, 2025)
Immobilized elderly are at high risk of developing pressure ulcers, which can impact their quality of life and increase the burden of family care. Pressure ulcer prevention is a crucial effort that must be optimally implemented by increasing the capacity of families as the primary caregivers. This community service activity aims to improve family knowledge and skills in providing pressure ulcer prevention care for immobilized elderly. The method used is education through interactive counseling and hands-on simulations on basic pressure ulcer prevention care, including position changes, skin care, bedding selection, and nutritional support. The activity was conducted at the Sri Kuncoro Community Health Center with 10 families caring for immobilized elderly people participating. The results showed an increase in the families' understanding of the concept of pressure ulcers and their skills in implementing preventive measures, as demonstrated by improved pre- and post-test scores and improved simulation practice skills. This activity is expected to empower families to implement independent and sustainable care to prevent pressure ulcers in immobilized elderly people.